Crystal structures, bond characteristics, and dielectric properties of novel middle-εr Ln3NbO7 (Ln = Nd, Sm) microwave dielectric ceramics with opposite temperature coefficients. Issue 24 (15th December 2022) - Bao, Jian; Guo, Weijia; Kimura, Hideo; Zhang, Yuping; Du, Jialun; Zhou, Yuanyuan; Ma, Yan; Wu, Haitao; Yue, Zhenxing
Abstract: This study synthesized two novel middle- ε r Ln3 NbO7 (Ln = Nd, Sm; named NNO and SNO) microwave dielectric ceramics through the classic solid-state process. The results of XRD and Rietveld refinement show that NNO and SNO ceramics formed pure phases with the space group Cmcm (63) and C2221 (20), respectively. The properties of Ln-O and Nb–O bonds of NNO and SNO ceramics were calculated based on the P–V–L theory. The Nb–O bonds positively affect the crystal structure stability of the two ceramics. The optimum microwave dielectric properties were obtained (NNO: ε r  = 31.61, Q·f  = 6, 615 GHz (at 6.10 GHz), and τ f  = −455.70 ppm/°C; SNO: ε r  = 34.55, Q·f  = 11, 625 GHz (at 5.77 GHz) and τ f  = 72.59 ppm/°C) when the samples sintered at 1550 °C. Notably, SNO ceramic shows a low dielectric loss and medium dielectric constant, and the opposite τ f of NNO and SNO ceramics provide the possibility to fabricate microwave dielectric devices with good temperature stability.